The INTERGROWTH‐21st gestational weight gain standard and interpregnancy weight increase: A population‐based study of successive pregnancies. Issue 6 (5th May 2017) - Hutcheon, Jennifer A.; Chapinal, Nuria; Bodnar, Lisa M.; Lee, Lily
Abstract : Objective: To link the INTERGROWTH‐21st gestational weight gain standard with the risks of excess maternal postpartum weight retention, approximated by women's weight change between successive pregnancies. Methods: A population‐based retrospective cohort study of 58, 534 women delivering successive pregnancies in British Columbia, Canada (2000‐2015) was conducted. Pregnancy weight gain (kg) in the index pregnancy was converted into a gestational age‐standardized z ‐score using the INTERGROWTH‐21st standard. Excess interpregnancy weight gain was defined as weight increases of 5 kg, 10 kg, or obesity (≥30 kg/m 2 ) at the next pregnancy. Weight gain z ‐scores and excess interpregnancy weight change were associated using logistic regression. Results: For all definitions of excess interpregnancy weight gain, risks remained low and stable below a weight gain z ‐score of 0 (50th percentile) but rose sharply with increasing z ‐scores above zero. Compared with women gaining −1 to 0 SD (16th to 50th percentiles), women gaining > 0 to +1 SD (51st to 84th percentiles) were 55% to 84% more likely to retain excess weight between pregnancies. Risks were three‐ to sixfold higher in women gaining >+1 SD. Conclusions: A large range of the INTERGROWTH‐21st percentiles were associated with increased risks of excess interpregnancy weight gain. The standard may normalize high weight gains of women at increased risk of excess weight retention.